2001
DOI: 10.1021/ma001990b
|View full text |Cite
|
Sign up to set email alerts
|

Ru(Cp*)Cl(PPh3)2:  A Versatile Catalyst for Living Radical Polymerization of Methacrylates, Acrylates, and Styrene

Abstract: Ru(Cp*)Cl(PPh3)2 (Cp* ) pentamethylcyclopentadienyl; PPh3 ) triphenylphosphine) has been found to be a versatile catalyst that is applicable to living radical polymerization of methyl methacrylate (MMA), methyl acrylate (MA), and styrene (St) with Al(Oi-Pr)3 as an additive. The numberaverage molecular weights (Mn) of the obtained polymers increased in proportion to monomer conversion, and the molecular weight distributions were very narrow (Mw/Mn < 1.1). Effective initiators were all alkyl halides (R-X), where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 31 publications
5
84
0
Order By: Relevance
“…The detailed studies of the metallocenes effect on the radical polymerization have been reported in [22][23][24][30][31][32][33][34][35][36][37][38][39][40][41][42][43], the considered metallocenes including complexes of iron [22, 23, 30-35, 39, 43], titanium [23, 36-38, 40, 41], zirconium [24,38,42,43], molybdenum [44,45], cobalt [46], ruthenium [47,48], etc.…”
mentioning
confidence: 99%
“…The detailed studies of the metallocenes effect on the radical polymerization have been reported in [22][23][24][30][31][32][33][34][35][36][37][38][39][40][41][42][43], the considered metallocenes including complexes of iron [22, 23, 30-35, 39, 43], titanium [23, 36-38, 40, 41], zirconium [24,38,42,43], molybdenum [44,45], cobalt [46], ruthenium [47,48], etc.…”
mentioning
confidence: 99%
“…Although this is a versatile system which gives very narrow molecular weight distributions, the polymerizations are slow and need over 100 h for completion. [62] …”
mentioning
confidence: 99%
“…Among the various strategies to increase the catalytic activity, the use of electron-donating ligands for ruthenium and iron catalysts, in which the lowered redox potential of the metal catalyst due to the ligands contributes to the activation of the carbon-halogen terminal, has proven effective. 9,10 For this approach, we have introduced electron-donating cyclopentadienyl derivative ligands, such as indenyl (Ind), 43 pentamethylcyclopentadienyl (Cp*) 44 and aminoindenyl 45 groups on the ruthenium complex, and found that they are effective for inducing fast and/or versatile living radical polymerizations of conjugated vinyl monomers (Figure 4). 46 Once these cyclopentadienyl-based ruthenium complexes were found to be better for living radical polymerizations, they were also successfully used for the Kharasch addition reaction of low-molecular weight compounds.…”
Section: Metal Catalytic Systemsmentioning
confidence: 99%
“…47,48 The ruthenium Cp*-complex [Ru(Cp*)Cl(PPh 3 ) 2 ] in particular gave well-controlled polymers with narrow molecular weight distributions (MWDs) from three different types of conjugated vinyl monomers, methyl methacrylate (MMA), methyl acrylate (MA) and St, via the reversible activation of the stable and relatively strong carbon-chlorine bond originating from the common initiator [H-(MMA) 2 -Cl] ( Figure 5). 44 The use of the C-Cl bond as the dormant species is better in comparison to the weaker and less stable C-Br and C-I bonds because it preserves the high chain-end functionality of the halide groups, which can be efficiently used for block copolymerization. Although it has not been verified that the lower redox potential guarantees a fast reversible interconversion between the dormant and active species, this strategy seems effective at least for a series of well-defined metal complexes with similar structures.…”
Section: Metal Catalytic Systemsmentioning
confidence: 99%